Tassa di soggiorno or tassa turistica? - Lenassi, Nives (Annales. Series historia et sociologia, 2024)
This article addresses bilingualism in Slovenian Istria, where both Slovenian and Italian are official languages, and it examines translations of administrative texts from the websites of four bilingual municipalities: Ankaran, Koper, Izola, and Piran. The study briefly reviews prior analyses whose findings served as the foundation for this research, and it outlines characteristic and widely used full-form lexical units as well as acronyms and abbreviations in normative and informative bilingual texts. It then discusses problems in terminological uniformity, proposing appropriate translation strategies to provide coherent use of terminology as well as clearer texts.
Keywords: abbreviation; acronym; corpora; Italian; Italijanščina; Kratice; Okrajšave; Prevajanje in tolmačenje; terminological uniformity; Terminologija; translation strategies